Using Public Food Grain Stocks to Enhance Food Security - World Bank (Washington, DC, 2012)
The recurrent global food price spikes in 2008 and 2010 rekindled interest in the use of national food grain stockpiles ('stocks') to enhance food security. They were a commonly used instrument in government responses to these food prices spikes. They were also widely considered as a useful tool after the 1974 food crisis and its associated food price volatility and supply disruptions. Large stocks became a reality at the global level in the 1980s and 1990s as a side-product of farm income support policies in the developed countries. However, large 'buffer' or 'intervention' stocks, as the grain accumulations in developed countries came to be called, eventually proved to be very costly forms of producer income support and were drawn down for fiscal and other reasons starting in the late 1990s. This report, prepared for government and development partner practitioners, revisits the issues and evidence concerning grain stocks. It starts with an open mind concerning stocks as policy tools and specifically seeks to avoid the polarization of views that grew up around the topic in the 1980s and 1990s. It takes the form of an evidence-based review of developing country experience. Historically, grain stocks have been used for two main purposes. First, to stabilize domestic prices and second, to provide readily available emergency food and safety net reserves targeted at the most vulnerable. The assessment of actual experience of using grain stocks for these two purposes is summarized as follows. Using grain stocks to stabilize domestic prices has generally not been an effective instrument to improve food security outcomes. Developed countries no longer use stocks to stabilize domestic prices due to the unpredictability and often unsustainably high budget costs. In Africa and Asia, where price stabilization programs are still frequently pursued, high fiscal costs are crowding out needed public investment in agricultural productivity and rural infrastructure. The often unpredictable grain purchases and releases of stabilization programs are discouraging private investment in both grain production and storage, which are the key to lowering both the level and volatility of food prices.